Chemical disinfection of Encephalitozoon cuniculi: toward evidence-based infection control guidelines - Gao, Jianhua; Meng, Xianzhi; He, Zhangshuai; Tang, Yunlin; Chen, Jie; He, Xuemei; Cao, Hua; Long, Shuyan; Pan, Guoqing (Frontiers in Microbiology, 2026)
BackgroundEncephalitozoon cuniculi is an opportunistic pathogen with significant zoonotic potential, particularly for immunocompromised individuals. However, evidence-based disinfection protocols against its environmentally resistant spores are lacking, leading to potential reliance on suboptimal agents.ObjectiveThis study aimed to establish a rigorous, data-driven hierarchy for the efficacy of common chemical disinfectants against E. cuniculi spores by integrating assessments of structural integrity, cellular infectivity, and in vivo dissemination.MethodsWe employed a multi-modal approach. Spores were treated with rapid-acting (75% ethanol, 1% hydrogen peroxide, chlorine-based agent) and long-acting (nano-silver, quaternary ammonium compounds—QACs) disinfectants. Sporicidal effects were evaluated via flow cytometry using ethidium bromide (EB) staining. Functional infectivity was quantified in Vero cells using a species-specific TaqMan qPCR assay targeting intracellular spore DNA. A murine model was used to assess the capacity of treated spores to establish systemic infection, quantified by spore DNA load in blood and kidney tissue.ResultsFlow cytometry revealed that 75% ethanol caused significant membrane damage (~51% EB-positive spores in 20 min) but failed to consistently abolish infectivity in cell culture or mice. Chlorine-based agents and hydrogen peroxide demonstrated potent, time-dependent inactivation, achieving >96 and 100% infectivity reduction in cells and mice, respectively, within 60 min. Notably, chlorine agents rendered spores non-infectious without inducing proportional EB uptake, indicating a mechanism distinct from gross membrane disruption. The long-acting disinfectant QACs necessitated an extended contact time (up to 5 h) to achieve complete prevention of in vivo infection. This prolonged exposure induced substantial spore aggregation, thereby impeding accurate flow cytometric analysis.ConclusionThe chlorine-based disinfectant and hydrogen peroxide (rapid-acting), as well as the quaternary ammonium compound (long-acting), all effectively eliminated the infectivity of E. cuniculi spores. Crucially, we demonstrate a critical dissociation between spore structural damage and viability, highlighting the necessity of functional infectivity assays over structural metrics alone. This study provides a foundational framework for evidence-based infection control guidelines in clinical, veterinary, and public health settings.